The importance of vaccines and their health impact on contemporary medicine in the story «Los barbones» - Hidalgo Manrique, Renzo Santiago (2022)
This article will analyse the story «Los barbones», a text that forms part of Ricardo Palma,s Tradiciones peruanas, which mentions the Hospitaller Order of the Bethlemites. The relationship between this order and the process of vaccination against smallpox in Peru at the beginning of the 19th century will be studied. It will also review how vaccination protects the human body from different diseases and the impact it has had on world health, as the technique of immunization revolutionized contemporary medicine. It will also examine the types of vaccines and the relevance of immunizations concerning the current situation of COVID-19.